2002
DOI: 10.1359/jbmr.2002.17.9.1629
|View full text |Cite
|
Sign up to set email alerts
|

Radius Bone Strength in Bending, Compression, and Falling and Its Correlation With Clinical Densitometry at Multiple Sites

Abstract: This study comprehensively analyzes the ability of site-specific and nonsite-specific clinical densitometric techniques for predicting mechanical strength of the distal radius in different loading configurations. DXA of the distal forearm, spine, femur, and total body and peripheral quantitative computed tomography (pQCT) measurements of the distal radius (4, 20, and 33%) were obtained in situ (with soft tissues) in 129 cadavers, aged 80.16 ؎ 9.8 years. Spinal QCT and calcaneal quantitative ultrasound (QUS) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 44 publications
2
36
0
1
Order By: Relevance
“…During the same period, spine BMD decreased, while hip BMD did not. In accordance, a number of prior studies confirmed that BV/TV is not altered on the basis of trans-iliac histomorphometry, and spine BMD decreases only slightly during the first (58). Third, the assumed tissue modulus (15 GPa) and Poisson ratio of 0.3 may not reflect the true values for individual subjects because these physical parameters can be dependent on the subject and anatomic site (36).…”
Section: Discussionsupporting
confidence: 52%
“…During the same period, spine BMD decreased, while hip BMD did not. In accordance, a number of prior studies confirmed that BV/TV is not altered on the basis of trans-iliac histomorphometry, and spine BMD decreases only slightly during the first (58). Third, the assumed tissue modulus (15 GPa) and Poisson ratio of 0.3 may not reflect the true values for individual subjects because these physical parameters can be dependent on the subject and anatomic site (36).…”
Section: Discussionsupporting
confidence: 52%
“…In order to asses this load-to-strength ratio, the activity or event associated with a fracture must be identified, and the applied load and bone strength for that event estimated. The ability of a bone to resist fracture at a given loading configuration depends not only on its mass but also on the spatial distribution of bone tissue and the intrinsic properties of bone material [2,10,35,51]. A recent study showed that the ratio of skeletal loading to bone strength indices, as assessed by QCT, explains the age-and sexspecific patterns of wrist and hip fractures better than does BMD [57].…”
Section: Discussionmentioning
confidence: 99%
“…However, the strength of long bones under axial compression has been shown to be predictive of failure stresses most typically occurring during a fall. 55 Finally, although it has been reported 31 that microdamage accounts for TB post-yield behavior as well, its effects were not explicitly considered in the proposed model since there is currently no imaging modality that can provide resolutions adequate to detect microdamage such as microcracks. Nevertheless, the yield and post-yield behavior predicted and which had previously been observed experimentally, are likely a manifestation of such microdamage.…”
mentioning
confidence: 99%